2016
DOI: 10.1159/000444145
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>FTO</i></b> Genotype Interacts with Improvement in Aerobic Fitness on Body Weight Loss During Lifestyle Intervention

Abstract: Objective: Not every participant responds with a comparable body weight loss to lifestyle intervention, despite the same compliance. Genetic factors may explain parts of this difference. Variation in fat mass and obesity-associated gene (FTO) is the strongest common genetic determinant of body weight. The aim of the present study was to evaluate the impact of FTO genotype differences in the link between improvement of fitness and reduction of body weight during a lifestyle intervention. Methods: We genotyped 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Previous work has shown that exercise intervention can ameliorate the influence of FTO risky alleles on BMI on the FTO rs8050136 SNP [ 8 , 9 ] and the rs9939609 SNP [ 10 12 ]. However, due to the direct influence of the FTO SNP rs1421085 on early adipocyte differentiation, the effect of exercise training on body fat in the risky allele carriers of the rs1421085 SNP are less certain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that exercise intervention can ameliorate the influence of FTO risky alleles on BMI on the FTO rs8050136 SNP [ 8 , 9 ] and the rs9939609 SNP [ 10 12 ]. However, due to the direct influence of the FTO SNP rs1421085 on early adipocyte differentiation, the effect of exercise training on body fat in the risky allele carriers of the rs1421085 SNP are less certain.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al carried out a systematic review and meta‐analysis confirming the association between the FTO rs9939609 risk allele and greater weight loss in response to diet/lifestyle interventions (Xiang et al, 2016). Among healthy subjects, after 9 months of lifestyle intervention, there was no statistically significant difference between genotype for the obesity risk variant in FTO (Sailer et al, 2016). Collectively, the conflicting results mentioned above may be ascribed to the study design, exercise programme, race and gender.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies suggest that physical activity plays a role in regulating FTO gene expression. It is worth noting that both Wang et al and Sailer et al [ 35 ] reported greater response to exercise in risk allele groups. This seems counterintuitive because the propensity to be overweight or obese is attributed to the risk alleles.…”
Section: Fto and Exercise Interventionsmentioning
confidence: 96%
“…Sailer et al [ 35 ] examined subject’s response to exercise as it related to FTO genotype. Subjects underwent a 9-month lifestyle intervention that included 3 h of moderate physical exercise per week and monthly sessions with a dietary counselor.…”
Section: Fto and Exercise Interventionsmentioning
confidence: 99%
See 1 more Smart Citation